Electrowetting-on-dielectric behavior of micro-nano hierarchical SiO2 layers decorated with noble metals. Issue 20 (15th October 2021) - Kim, Jae-Hun; Mirzaei, Ali; Lee, Jae-Hyoung; Kim, Jin-Young; Wu, Ping; Kim, Hyoun Woo; Kim, Sang Sub
Abstract: The performances of electrowetting-on-dielectric (EWOD) devices were investigated using micro-nano hierarchical structures of pristine and noble metal-decorated SiO2 layers, with the entropy wetting model. The SiO2 layers were prepared by an electrospray technique, and noble metals were decorated by UV irradiation. In addition, a thin Teflon coating was applied to enhance their initial hydrophobicity. The initial water contact angle (WCA) value of the Pd-decorated SiO2 (Pd–SiO2 ) and Ag-decorated SiO2 (Ag–SiO2 ) layers was 165°, while that of the Au-decorated SiO2 (Au–SiO2 ) and pristine SiO2 layers was 154°. Different external voltages (up to 200 V) were used to investigate the EWOD behavior of the fabricated layers. In all cases, the WCA decreased with increasing applied voltage. Under 200 V (maximum applied voltage), WCA values of 129, 120, 115, and 102° were measured for pristine SiO2, Pd–SiO2, Ag–SiO2, and Au–SiO2 layers, respectively. Moreover, the EWOD properties of the noble metal-decorated layers were studied in the presence of dodecane oil. At 200 V, the WCAs of the Pd–SiO2, Ag–SiO2, Au–SiO2, and layers were 134, 97 and 100°, respectively. Finally, we applied the entropy wetting model to further understand the results of the EWOD experiments.